SCAMPs highlight the developing cell plate during cytokinesis in tobacco BY-2 cells - Lam, Sheung Kwan; Hillmer, Stefan; Robinson, David G. (2008)
We previously demonstrated that rice (Oryza sativa) SECRETORY CARRIER MEMBRANE PROTEIN1 (OsSCAMP1)-yellow fluorescent protein in transgenic tobacco (Nicotiana tabacum) Bright Yellow-2 cells locates to the plasma membrane and to motile punctate structures, which represent the trans-Golgi network/early endosome and are tubular-vesicular in nature. Here, we now show that SCAMPs are diverted to the cell plate during cytokinesis dividing Bright Yellow-2 cells. As cells progress from metaphase to cytokinesis, punctate OsSCAMP1-labeled structures begin to collect in the future division plane. Together with the internalized endosomal marker FM4-64, they then become incorporated into the cell plate as it forms and expands. This was confirmed by immunogold electron microscopy. We also monitored for the Golgi apparatus and the prevacuolar compartment (PVC)/multivesicular body. Golgi stacks tend to accumulate in the vicinity of the division plane, but the signals are clearly separate to the cell plate. The situation with the PVC (labeled by green fluorescent protein-BP-80) is not so clear. Punctate BP-80 signals are seen at the advancing periphery of the cell plate, which was confirmed by immunogold electron microscopy. Specific but weak labeling was observed in the cell plate, but no evidence for a fusion of the PVC/multivesicular body with the cell plate could be obtained. Our data, therefore, support the notion that cell plate formation is mainly a secretory process involving mass incorporation of domains of the trans-Golgi network/early endosome membrane. We regard the involvement of multivesicular late endosomes in this process to be equivocal.